A traC mutant that retains sensitivity to f1 bacteriophage but lacks F pili. - Schandel, K A (1987)
An F lac pro mutant which was temperature sensitive for infection by the filamentous bacteriophage f1 but resistant to the F-specific icosahedral RNA phage f2 was isolated. Cells carrying the F' mutation failed to elaborate F pili at all temperatures. Mutant cells were able to pair with recipient cells during bacterial conjugation, but transfer of conjugal DNA occurred at a greatly reduced frequency. Complementation analyses showed the F' mutation to be in the traC gene. When a plasmid carrying traC was introduced into hosts harboring the F' mutation, phage sensitivity, the ability to elaborate F pili, and conjugation efficiency were restored. The mutation was named traC1044. The F lac pro traC1044 mutant appears to be unique among traC mutants in retaining host sensitivity to the filamentous phage f1 in the absence of expression of extended F pili. Phage f1 attachment sites appeared to be present at the cell surface in traC1044 mutants. The reduced accessibility of these sites may account for the reduced efficiency of phage f1 infection of traC1044 hosts, although the possibility that a defect was present in the receptor site itself was not eliminated. Membranes of hosts carrying the F' mutation contained a full complement of mature F-pilin subunits, so the product of traC is presumably required for pilus assembly but not for pilin processing. This, together with the deficiency in conjugal DNA transfer, suggests that traC may be part of a membrane-spanning tra protein complex responsible for pilus assembly and disassembly and conjugal DNA transmission.